WTO agreements : deficiencies, imbalances and required changes (Zed Books LondonGB, 1998)
Gives an account of the severe overall imbalance in the concessions made by the developing countries and the developed countries in the Uruguay Round results. Discusses how the recent trend in the WTO is towards enhancing the imbalance, rather than taking corrective steps to reduce it. Takes up specific subjects for discussion and analysis e.g. the dispute settlement process; market access; unfair trade practices, agriculture and textiles; services; and, intellectual property rights.\n
Keywords: TRADE AGREEMENTS